1985
DOI: 10.1007/bf02016812
|View full text |Cite
|
Sign up to set email alerts
|

The detection and characterization of bacteria-sized protists in “Protist-free” filtrates and their potential impact on experimental marine ecology

Abstract: Nuclepore filters of 0.6-1.0μm pore size have been used to prepare "protist-free" water for a number of studies in microbial ecology. This procedure has been called into question by a recent study claiming that a significant portion of bacterial loss in filtrates could be due to uncharacterized predators passing through 0.6μm filters. We were unable to directly observe protists in 0.6μm filtrates using phase contrast, epifluorescence, or transmission electron microscopy. Using the culture techniques of rice gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Freshly collected samples were filtered through Nuclepore filters (1 pm pore-size) to reduce grazers, phytoplankton and detritus in relation to the bacteria. To promote bacterial growth (Ammerman et al 1984) and reduce grazing by bacterivores passing the 1 pm Nuclepore filter (Fuhrman & MacManus 1984, Cynar et al 1985, filtered samples were diluted 1 9 with 0.22 pm pore-size filtered seawater from the same site (Tremaine & Mills 1987). The diluent was prepared by filtration through either a Gelman Acruflux cartridge (0.2 pm pore-size, fed by peristaltic pump) or a Millipore filter (0.22 pm poresize, vacuum of i 15 cm Hg).…”
Section: Methodsmentioning
confidence: 99%
“…Freshly collected samples were filtered through Nuclepore filters (1 pm pore-size) to reduce grazers, phytoplankton and detritus in relation to the bacteria. To promote bacterial growth (Ammerman et al 1984) and reduce grazing by bacterivores passing the 1 pm Nuclepore filter (Fuhrman & MacManus 1984, Cynar et al 1985, filtered samples were diluted 1 9 with 0.22 pm pore-size filtered seawater from the same site (Tremaine & Mills 1987). The diluent was prepared by filtration through either a Gelman Acruflux cartridge (0.2 pm pore-size, fed by peristaltic pump) or a Millipore filter (0.22 pm poresize, vacuum of i 15 cm Hg).…”
Section: Methodsmentioning
confidence: 99%
“…The number of heterotrophic nanoflagellates in the < 1 pm filtrate did not increase during the incubation, which implies that the flagellates either were damaged after being squeezed through 1 pm pores, or were filtrate (Fuhrman & McManus 1984, Cynar et al 1985, was minor. The study of Wikner & Hagstrom (1988) from the Baltic Sea also showed that the flagellate predation rate decreases sharply in < 1 pm water sample.…”
Section: Heterotrophic Nanoflagellates In the Filtratesmentioning
confidence: 99%
“…Radioisotope techniques suffer from several limitations including artifacts arising from isotopic label leaking into the medium. Methods for estimating predation that assume predator-free filtrates after filtration through > 0.4 pm Nuclepore filters (Wright & Coffin 1984) are suspect, since such filtration permits the passage of flagellates capable of significant bacterivory (Cynar et al 1985a). The interpretation of grazing rates obtained with any of these indirect methods, in which the fate of the prey is not observed microscopically, is burdened by several potentially faulty assumptions.…”
Section: Introductionmentioning
confidence: 99%